Increasing production diversity and diet quality through agriculture, gender, and nutrition linkages: A cluster-randomized controlled trial in Bangladesh - Ahmed, Akhter; Coleman, Fiona M.; Ghostlaw, Julie; Hoddinott, John F.; Menon, Purnima; Parvin, Aklima; Pereira, Audrey; Quisumbing, Agnes R.; Roy, Shalini; Younus, Masuma (International Food Policy Research Institute, 2022)
A growing body of evidence indicates that agricultural development programs can potentially improve production diversity and diet quality of poor rural households; however, less is known about which aspects of program design are effective in diverse contexts and feasible to implement at scale. We address this issue through an evaluation of the Agriculture, Gender, and Nutrition Linkages (ANGeL) project. ANGeL is a randomized controlled trial testing what combination of trainings focused on agricultural production, nutrition behavior change communication, and gender sensitization were most effective in improving production diversity and diet quality among rural farm households in Bangladesh. We find that trainings focused on agriculture improved production diversity in terms of greater production of fruits and vegetables grown on the homestead, eggs, dairy, and fish; adding trainings on nutrition and gender did not significantly change these impacts. Trainings focused on both agriculture and nutrition showed the largest impacts on diet quality, with evidence indicating that households in this arm also significantly increased consumption out of homestead production for fruits and vegetables, eggs, dairy, and fish. Findings indicate that agricultural training that promotes production of diverse, high-value, nutrient-rich foods can increase production diversity, and this can improve diet quality, but diet quality impacts are larger when agricultural training is combined with nutrition training. Relative to treatments combining agriculture and nutrition training, we find no significant impact of adding the gender sensitization on our measures of production diversity or diet quality.